Occurrence and management of herbicide resistance in annual vegetable production systems in North America. Issue 5 (5th September 2022) - Boyd, Nathan S.; Moretti, Marcelo L.; Sosnoskie, Lynn M.; Singh, Vijay; Kanissery, Ramdas; Sharpe, Shaun; Besançon, Thierry; Culpepper, Stanley; Nurse, Robert; Hatterman-Valenti, Harlene; Mosqueda, Elizabeth; Robinson, Darren; et al.
Abstract: Herbicide resistance has been studied extensively in agronomic crops across North America but is rarely examined in vegetables. It is widely assumed that the limited number of registered herbicides combined with the adoption of diverse weed management strategies in most vegetable crops effectively inhibits the development of resistance. It is difficult to determine whether resistance is truly less common in vegetable crops or whether the lack of reported cases is due to the lack of resources focused on detection. This review highlights incidences of resistance that are thought to have arisen within vegetable crops. It also includes situations in which herbicide-resistant weeds were likely selected for within agronomic crops but became a problem when vegetables were grown in sequence or in adjacent fields. Occurrence of herbicide resistance can have severe consequences for vegetable growers, and resistance management plans should be adopted to limit selection pressure. This review also highlights resistance management techniques that should slow the development and spread of herbicide resistance in vegetable crops.